Analisis Pengaruh Tingkat Bagi Hasil dan Tingkat Suku Bunga Terhadap Deposito Mudharabah (Studi kasus pada PT. Bank Muamalat Indonesia, tbk.) - Ika Irmawati (Economy Deposit Journal (E-DJ), 2023)
This study aims to determine (1) the level of profit sharing has a positive and significant effect on mudharabah deposits. (2) The interest rate has a negative and significant effect on mudharabah deposits. The research data is data sourced from the monthly reports of PT Bank Muamalat Indonesia and Bank Indonesia's monthly data. The data obtained were analyzed by multiple regression.This research is a case study of PT. Bank Muamalat Indonesia, Tbk. The population in this study is the balance sheet financial statements of PT. Bank Muamalat and Bank Indonesia data regarding mudharabah deposits, profit sharing rates and interest rates. While the sample used in this study is the monthly data on the balance sheet financial statements of PT. Bank Muamalat and Bank Indonesia data regarding mudharabah deposits, profit sharing rates and interest rates during 2020-2022. The variables studied in this study include profit sharing rates, interest rates, and mudharabah deposits. The data collection method used is documentation.The results of this study indicate that there is a positive and significant effect of the level of profit sharing on mudharabah deposits. And the interest rate has a negative and significant effect on mudharabah deposits.